Tuanku Imam Bonjol's Intellectual Contribution through the Padri Movement - Amril, Amril; Ramananda, Vici (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This article discusses Tuanku Imam Bonjol's intellectual contribution to the struggle for Indonesian independence. Tuanku Imam Bonjol is an intellectual figure in the Padri movement’s practical politics who is not careless and always makes sensible and wise decisions. This research uses descriptive qualitative research methods. Tuanku Imam Bonjol’s struggle against the Dutch colonialists was not only to liberate Minangkabau land from Dutch colonialism but also a form of jihad to re-establish Islamic law in Minangkabau land. Tuanku Imam Bonjol’s adherence to the Wahhabi ideology did not drive him to commit acts of violence. Tuanku Imam Bonjol still conveyed it rationally according to the context of that time. Tuanku Imam Bonjol responded wisely to the social conditions of the Minangkabau people amidst many people who did not follow Islamic law. As time passed, he realized that the tough attitude of the Padri movement, initially aimed at upholding Islamic law, had exacerbated the conflict between the Padri and the Indigenous people, making Imam Bonjol abandon the Wahhabi ideology that he had adhered to all this time. The legacy of Tuanku Imam Bonjol and the Padri movement in Minangkabau history was immense. They left traces of struggle that inspired subsequent generations to fight for independence and defend Islamic values and local culture.